Digital System Innovation to Strengthen the Constitutional Court in Managing Simultaneous Election Disputes Indonesia - Tarmudi; Saragih, Geofani Milthree; Fauzan Ghafur; Indana Zulfah; Zean Via Aulia Hakim (Pandecta Research Law Journal, 2025)
This study examines the overburdening of the Constitutional Court (MK) due to the high volume of regional head election (pilkada) disputes, which has led to case backlogs, reduced legal efficiency, and increased state expenditures. Although institutions like Bawaslu and PTUN also have authority to resolve these disputes, many cases are submitted directly to MK, bypassing other mechanisms. Using a normative juridical method that includes legal analysis, historical context, comparative law, and case studies, the research evaluates previous dispute resolution practices and proposes a digitalization-based reform. Key challenges identified include procedural inefficiencies, high costs, and a lack of institutional coordination. The current system is viewed as suboptimal, with many disputes producing outcomes that fail to satisfy parties involved. To address these issues, the study proposes a digital platform aimed at streamlining the resolution process through integrated case registration, document submission, and inter-agency coordination. This system would reduce MK’s caseload, cut operational costs, and enhance transparency and accountability via real-time monitoring. By reinforcing the roles of Bawaslu and PTUN, the platform could help redistribute dispute resolution authority more effectively. The study concludes that digital transformation offers a viable solution to improve the efficiency, fairness, and cost-effectiveness of pilkada dispute resolution in Indonesia.